Bi-directional DC-AC using BLDC motor for electric and hybrid electric vehicles applications with reduced number of switches - Arokianathan, Nishalini Delcy; Josh, Francis Thomas; Brindha, Evelyn; Joseph, Jeyaraj Jency; Das, Raman Mohan; Kannadhasan, Suriyan (Institute of Advanced Engineering and Science, 2024)
Electric scooters often have a single design and are difficult to produce at a greater level than other forms of transportation. A possible cut electric scooter is built with the optimization design of the vehicle combustible wealth and the pollution characteristics in order to arrange to a correct solution by resolving each and every challenge. The engines' electrical systems are comprised of lead acid batteries. For the sake of a straightforward simulation procedure, the engine operates in two states ON and OFF while the vehicle's speed is regulated in three ranges roughly corresponding to high, medium, and low. The planetary speed ratio and the final drive speed ratio are gathered in the computation method's general outline. Utilizing simulation MATLAB, the findings of optimization strategies are resolved. This technique improves the fuel plenty and discharge quality of the possibility cut electric automobiles.